2014
DOI: 10.1353/ff.2014.0015
|View full text |Cite
|
Sign up to set email alerts
|

The Magnifying Effect of Privilege: Earnings Inequalities at the Intersection of Gender, Race, and Nativity

Abstract: Feminist concerns about the epistemological problems of quantitative methods have resulted in an underdevelopment of quantitative approaches that could contribute to existing intersectional theory. Further, feminist scholars commonly consider the effects of gender as it intersects with race or class, but relatively little of this research has included nativity (being either an immigrant or native-born to a society). This article addresses these shortcomings by examining patterns of earnings inequality at the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…However, results are mixed as to what effect gender has compared with race/ethnicity or nativity. Many scholars have found that gender disparities in earnings are consistently larger than racial or nativity disparities (Avalos 1996;Greenman and Xie 2008;Nawyn and Gjokaj 2014;Sullivan 1984). However, in her study of earnings inequality for highly skilled immigrant women, Lopez (2012) found that nativity status explains more of the earnings gap with U.S.-born men than does gender status.…”
Section: Gender Revolution and Second-generation Womenmentioning
confidence: 96%
“…However, results are mixed as to what effect gender has compared with race/ethnicity or nativity. Many scholars have found that gender disparities in earnings are consistently larger than racial or nativity disparities (Avalos 1996;Greenman and Xie 2008;Nawyn and Gjokaj 2014;Sullivan 1984). However, in her study of earnings inequality for highly skilled immigrant women, Lopez (2012) found that nativity status explains more of the earnings gap with U.S.-born men than does gender status.…”
Section: Gender Revolution and Second-generation Womenmentioning
confidence: 96%
“…Recall also Nawyn and Gjokaj's (2014) argument that there is a magnifying effect of privilege for members of multiple advantaged groups. Nevertheless, we suspect that that the questions we raise and the solutions we propose (see Footnote 27) may be adapted to address Alexander-Floyd's interpretation of intersectionality.…”
Section: A Commitment To Focusing On Women Of Color?mentioning
confidence: 99%
“…A fundamental premise in both these approaches is that an individual's identity is "more than a dummy variable" and treating it solely as an independent variable recognizes its influence on social, economic and cultural forces, and institutions, but ignores the determination of each of these factors on an individual's identity (Figart 1997). Much of this work has verified discrimination contains both a gender and racial component that cannot be decoupled because perceptions of race and gender are interdependent (Harnois and Ifatunji 2011;Ifatunji and Harnois 2016;Nawyn and Gjokaj 2014) yet this has left the experiences of American Indian and Alaska Native 1 (AIAN) women unexplored. We seek to fill this gap in the literature by documenting differences in the average and distribution of hourly earnings between AIAN women and men associated with identifying as AIAN alone or in 1 We use American Indian, Alaska Native, Native American and Indians interchangeably to refer to individuals who maintain a tribal affiliation or community attachment to any of the original peoples of North America.…”
Section: Introductionmentioning
confidence: 99%